Removal of calcium ions from water by selective electrosorption using target-ion specific nanocomposite electrode. (1st September 2019) - Kim, Jun; Jain, Amit; Zuo, Kuichang; Verduzco, Rafael; Walker, Shane; Elimelech, Menachem; Zhang, Zhenghua; Zhang, Xihui; Li, Qilin
Abstract: Technologies capable of selective removal of target contaminants from water are highly desirable to achieve "fit-for-purpose" treatment. In this study, we developed a simple yet highly effective method to achieve calcium-selective removal in an electrosorption process by coating the cathode with a calcium-selective nanocomposite (CSN) layer using an aqueous phase process. The CSN coating consisted of nano-sized calcium chelating resins with aminophosphonic groups in a sulfonated polyvinyl alcohol hydrogel matrix, which accomplished a Ca 2+ -over-Na + selectivity of 3.5–5.4 at Na + :Ca 2+ equivalent concentration ratio from 10:1 to 1:1, 94 – 184% greater than the uncoated electrode. The CSN coated electrode exhibited complete reversibility in repeated operation. Mechanistic studies suggested that the CSN coating did not contribute to the adsorption capacity, but rather allowed preferential permeation of Ca 2+ and hence increased Ca 2+ adsorption on the carbon cathode. The CSN-coated electrode was very stable, showing reproducible performance in 60 repeated cycles. Graphical abstract: Image 1 Highlights: A nanocomposite electrode selectively adsorbs Ca 2+ in the presence of Na + . Ca 2+ ion preferentially transported through the ion-selective nanocomposite coating. The electrode exhibits stable long-term performance in capacity and selectivity.